EVALUASI KONDISI PERKERASAN JALAN MENGGUNAKAN METODE SURFACE DISTRESS INDEX (SDI) PADA RUAS JALAN RANDEGAN LOR-TAMAN BENDUNG SLINGA KABUPATEN PURBALINGGA - Sihtasari Devi; Andyka Meylina (UNIVERSITAS AL WASHLIYAH (UNIVA) MEDAN, 2026)
Road infrastructure plays an important role in supporting community mobility and regional economic growth. Inadequately treated pavement deterioration can reduce road service quality and increase accident risks. This study aims to identify pavement distress types, analyze the factors causing deterioration, and determine appropriate maintenance methods using the Surface Distress Index (SDI) approach. The study was conducted on the Randegan Lor-Taman Bendung Slinga Road Section, Purbalingga Regency, with a total observation length of 300 meters divided into six segments. The research employed field surveys and descriptive quantitative analysis based on the SDI method established by the Directorate General of Highways. The analyzed parameters included crack area, crack width, pothole quantity, and rutting depth. The results indicated that the dominant pavement distresses were alligator cracking, edge cracking, depression, potholes, and ravelling. The primary factors causing pavement deterioration were repeated traffic loading, poor drainage systems, and inadequate shoulder support. The SDI analysis showed an average value of 85 for all segments, indicating a moderate pavement condition. Therefore, periodic maintenance consisting of sealing, levelling, and overlay treatments is recommended to prevent further pavement deterioration.